LIFE SKILLS ENHANCEMENT FOR PSYCHOACTIVE SUBSTANCE USE REDUCTION AMONG SCHOOL GOING ADOLESCENTS IN KENYA - Waithima, Charity (PEOPLE: International Journal of Social Sciences, 2017)
The aim of this study was to evaluate the effectiveness of life skills enhancement on substance use reduction among school going adolescents in Nyeri, Kenya. The study was a quasi-experimental quantitative study.Life skills’ enhancement was employed for six months. Purposive and simple random sampling techniques were used to select participants (n=1010) at baseline with experimental (n=454) and control (n=556) groups. A self-administered socio-demographic questionnaire and the Global School-based Student Health Survey tool were used to get data. Odds Ratio (OR)and 95% Confidence Interval (CI) brought out the estimated strength of association between independent variables and the dependent variable. Efficacy of the intervention was assessed after six months within and between groups at endline with reference to baseline using Pearson’s chi-square. The overall current prevalence of substance use at baseline was 48.7%. In addition, there was a significant difference in reduction of substance use in the experimental group after intervention. It emerged that an adolescent enrolled in the experimental group was 86% times less likely to use any psychoactive substance compared to one in the control group. Life skills when enhanced were therefore found to be effective in empowering adolescents to develop safe and healthy behavior with regard to substance use. It is therefore recommended that education stakeholders in Kenya adapt the life skills enhancement strategy towards substance use reduction. Since the life skills enhancement training model was successful in Nyeri, there is need to expand it within the East Africa region and the rest of Africa.